Implementasi Teori Kognitif dan Konstruktivisme dalam Pembelajaran bagi Peserta Didik - Habsy, Bakharudin All; Zakirah, Amirah; Rahmah, Mutia Aulia; Nafisah, Candara Aulia (Lembaga Yasin AlSys, 2024)
This research aims to find out how cognitive theory and constructivism are applied in learning for students. The method used in this research is the method of distributing questionnaires and data collection techniques through literature studies from various sources and websites on the internet through journals, documents, books, etc. that are relevant to the topic, namely related to the implementation of cognitive theory. and constructivism theory in learning. Cognitive theory emphasizes the active role of students in processing information and their own understanding, while the constructivist approach emphasizes learning that occurs through social interactions and students' personal experiences. The results of this research can provide important insights for educators, policy makers and researchers who are interested in optimizing the implementation of cognitive theory and constructivism to improve student learning outcomes in the context of modern education.